Brillouin microscopic depth-dependent analysis of corneal crosslinking performed over or under the LASIK flap. Issue 11 (November 2020) - Zhang, Hongyuan; Roozbahani, Mehdi; Piccinini, Andre L.; Hafezi, Farhad; Scarcelli, Giuliano; Randleman, J. Bradley
Abstract : The standard CXL technique for treatment after LASIK flap creation generates significantly greater stiffening effect in the anterior cornea than a modified protocol with riboflavin administration under the LASIK flap. Abstract : Purpose: To determine the impact of corneal crosslinking (CXL) performed over the laser in situ keratomileusis (LASIK) flap using the Standard CXL (S-CXL) protocol or under the flap after flap lift (flap-CXL) on regional corneal stiffness using Brillouin microscopy. Setting: University of Southern California Keck School of Medicine, Los Angeles, California, and Cole Eye Institute, Cleveland Clinic, Cleveland, Ohio, USA. Design: Laboratory ex vivo experiment. Methods: After epithelium debridement, LASIK flaps were created on intact fresh porcine eyes with a mechanical microkeratome. Then, S-CXL (riboflavin applied to the corneal surface followed by 3 mW/cm 2 ultraviolet exposure with the flap in place for 30 minutes) or flap-CXL (riboflavin applied to the stromal bed after reflecting the flap followed by the same ultraviolet A exposure with the flap replaced) was performed. Depth profile of stiffness variation and averaged elastic modulus of anterior, middle, and posterior stroma were determined by analyzing Brillouin maps. Each eye served as its own control. Results: The study was performed on 24 fresh porcine eyes. S-CXL had maximal stiffening impact in the anterior most corneal stroma within the LASIK flap (8.40 ± 0.04 GHz), whereas flap-CXL had lower maximal stiffening impact (8.22 ± 0.03 GHz) ( P < .001) that occurred 249 ± 34 μm under the corneal surface. S-CXL increased longitudinal modulus by 6.69% (anterior), 0.48% (middle), and −0.91% (posterior) as compared with flap-CXL, which increased longitudinal modulus by 3.43% (anterior, P < .001), 1.23% (middle, P < .1), and −0.78% (posterior, P = .68). Conclusions: The S-CXL technique generated significantly greater stiffening effect in the anterior cornea than a modified protocol with riboflavin administration under the flap (flap-CXL). Minimal stiffening occurred in the middle or posterior cornea with either protocol.